The INFLUENCE OF FINANCIAL LITERACY, MOTIVATION, AND SOCIAL ENVIRONMENT ON SAVING DECISIONS: PENGARUH FINANCIAL LITERACY, MOTIVATION, DAN SOCIAL ENVIRONMENT TERHADAP KEPUTUSAN MENABUNG - Risti Gusmirah; Rahmawati Azizah -; Syara Purnama Sari; Shafitranata Shafitranata (Sekolah Tinggi Ilmu Ekonomi Al-Madani, 2025)
Saving is one of the main points for building a profitable economy, this is because it can be useful as an emergency fund or to avoid unexpected expenses. The decision to save is a choice for many people in allocating their finances to whom, meaning that saving can be done by anyone, including students. The aim of this research is to examine the influence of financial literacy, motivation and social environment on savings decisions made by students in Bandar Lampung City. This research uses quantitative data, with a questionnaire distributed via Google Form. The amount of data used was 130 respondents. The sampling technique is probability sampling using simple random sampling. Multiple linear regression data analysis method using SPSS 26 software. The research results show that motivation and social environment have a significant effect on the decision to save, while financial literacy has no effect on the decision to save for students in Bandar Lampung City.